Analisis Studi Kesenjangan Infrastruktur di Kawasan Pusat Permukiman pada Kelurahan Dasan Agung dan Kekalik Jaya Kota Mataram - Lalu Muhammad Faqih Firmansyah; Hilma Luthfia; Ferawati Fajrin; Muhammad Julfi Zahari; Iva Nur Ilmi; Giska Ayu Pradana Putri Kamase (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2025)
This study analyzes infrastructure disparities in the settlements of Dasan Agung and Kekalik in Mataram City. Although both are located in the city center, they exhibit different infrastructure conditions. The study compares the physical conditions and basic services in both areas and identifies the factors causing these disparities to support equitable and sustainable settlement planning. A qualitative-comparative case study method was used, involving observations and in-depth interviews. Quantitative analysis was conducted through scoring key infrastructure variables: roads, drainage, clean water, and electricity. The results show that Dasan Agung has an average score of 29% (poor), while Kekalik Jaya scores 54% (fair). Although the total aggregate scores appear similar, the distribution of scores across indicators reveals significant disparities. Dasan Agung performs better in road layout, but its physical condition is poor due to lack of maintenance. Its drainage system frequently floods due to open and clogged channels, in contrast to Kekalik's more efficient system. While clean water and electricity scores are identical, Kekalik provides more stable and legal services. These disparities are influenced by weak supervision and spatial planning policies that have not reached self-built settlements. The findings reflect Todaro and Smith’s theory and highlight obstacles to achieving SDGs 9 and 11.